ANALISIS BAHAN AJAR SASTRA DALAM BUKU TEKS BAHASA INDONESIA SMP/MTs KELAS VII - Suparti, Suparti; Suryaman, Maman (Diksi, 2018)
(Title: An Analysis of Literary Materials in Indonesian Textbook to Junior Hig School/MTs VII). This study attempted to describe (1) knowledge aspects of literary teaching materials; (2) skill aspects of literary teaching materials; and (3) attitude aspects of literary teaching materials in Indonesian textbook for Junior Hig School/MTs VII grades by using education character approach. This research used qualitative descriptive approachment type of document analysis. The source of the research data was based on  the Indonesian textbook of SMP/MTs VII. The technique to collect the data was done by reading and recording technique by using instrument which had been validated in the form of document analysis guide. The research data were analyzed using Miles and Hubermen model which included data reduction, presentation, and conclusion. The results of this study indicated that the knowledge, skills, and attitude aspect of literary materials had fulfilled in the Indonesian textbook for SMP/MTs VII with details (1) based on knowledge aspect of literary materials, the conceptual knowledge was more dominated than factual and procedural knowledge, (2) based on skills aspects of literary materials, the reading skills most often taught than listening, speaking, and writing skills; and (3) based on attitude aspects literary materials, the social attitudes is more dominated than spiritual attitudes.Keywords: literary materials, textbooks, character education.